Centering Critical Engagement, Multimodal Learning, and Compassion through Language and Literacy - Mulcahy, Cara; Shaw, Louise (The Intersections of Critical Pedagogy, Critical Literacy, and Social Justice: Toward Empowerment, Equity, and Education for Liberation, 2024)
Keywords: dept.sed

Autism spectrum disorder in adolescents and adults: an introduction - Volkmar, Fred R.; Reichow, Brian; McPartland, James C. (Adolescents and Adults with Autism Spectrum Disorders, 2024)
Leo Kanner’s classic description of autism appeared eight decades ago. Although the pace of research has increased dramatically, research specifically focused on adolescents and adults remains limited in many respects. Numerous outcome studies have been conducted and suggest potential for markedly improved outcome with intervention. Unfortunately, studies on adults after early adulthood are sparse and, for old age, almost nonexistent, reflecting a lack of support for research in this population. This is in stark contrast to other developmental disorders in which considerable information on adult life is often available. This book summarizes work across areas, focusing on what is known and not yet known, highlighting important areas for future research. While overall outcome has improved, a small group of individuals remain in need of high levels of adult care. For all individuals, the field requires new approaches to both research and clinical service.
Keywords: Adolescents; Adults; Autism; Outcome; Supports; dept.sed

Promoting awareness of social justice issues through technology-mediated project-based language learning - Gleason, Jesse S.; Suvorov, Ruslan (Advocating for Sociolinguistic Justice in the United States, 2024)
This chapter aimed at exploring how technology-mediated project-based language learning (PBLL) could be leveraged to foster 24 language learners’ awareness of social justice issues. Specifically, the study examined students’ perceptions regarding the potential benefits and challenges of technology-mediated PBLL for promoting social justice in a Spanish course. We used a grounded, iterative design and Teacher Action Research to analyze the data that comprised student-generated products (i.e., memes and written descriptions) and students’ perceptions of the benefits and challenges of using social justice projects in a Spanish course. In addition to revealing an array of perceived benefits and challenges of social justice projects for learning Spanish, the findings suggested the importance of using short, authentic multimodal texts and providing micro-scaffolding.
Num Pages: 23
Keywords: dept.sed

Autism spectrum disorders - Volkmar, F.R.; Reichow, B.; Wiesner, L.A. (Encyclopedia of Adolescence, Second Edition: Volumes 1-3, 2024)
This article addresses advances in the definition, diagnosis, and clinical features of ASD particularly as they affect adolescents. While advances in early diagnosis and treatment of autism have led to substantial improvements in outcomes (e.g., significantly higher levels of personal self-sufficiency and independence), challenges for adolescents with autism spectrum disorders (ASD) remain. Persistent social-communication abilities and intellectual disabilities can hamper prospects of future employment and increase risk for psychopathology including depression and mood disorder and issues surrounding gender identity. Biological issues emerge, as well, for many adolescents with ASD such as increased risk for seizure disorder. In comparison to the literature on preschool and school age children, the research base is much more limited for adolescents, and studies are needed to identify effective, evidence-based, intervention strategies for this population. © 2024 Elsevier Inc. All rights are reserved.
Keywords: Asperger's syndrome; Autism; Autism spectrum disorder; Neurodiversity; Not otherwise specified; Pervasive developmental disorder; dept.sed

Students with intellectual disabilities - Gerber, B.L. (Reaching and Teaching Students with Special Needs Through Art, 2024)
This chapter provides information about the changing definition and views of intellectual disabilities that impact both classroom placement and education programs. It describes learning characteristics of student with intellectual disabilities that are quite "normal" and predictable for them, and task analysis, a most effective special education teaching approach that demonstrates how to address those learning characteristics. © 2025 National Art Education Association. All rights reserved.
Keywords: dept.sed

Troubleshooting the art lesson - Gerber, B.L. (Reaching and Teaching Students with Special Needs Through Art, 2024)
Troubleshooting is a process designed to help teachers choose lessons, analyze their language and procedures, and organize classroom space and time. When an art lesson is planned, a logical expectation is that the lesson will go pretty much as written. Troubleshooting takes the opposite approach. It expects that things will go wrong and tries to prevent or minimize potential problems. "Murphy's Law" leads us to expect that whatever can go wrong will go wrong. The troubleshooting expectation that things will go wrong is the "Murphy's Law" of lesson planning. © 2025 National Art Education Association. All rights reserved.
Keywords: dept.sed

Reaching and teaching students with autism spectrum disorder - Eren, R.B.; Loesl, S.D.; Abraham-Braff, L.; Rudne, M.R. (Reaching and Teaching Students with Special Needs Through Art, 2024)
It is important to remember that autism spectrum disorder is a spectrum disorder that represents many individuals who have a wide and disparate range of challenges and strengths. There is an old adage that says, "If you have met one person with autism, then you have met one person with autism," for no two individuals on the spectrum will be exactly alike and present with the same strengths and challenges. This wide spectrum, or great variability within individuals on the spectrum, can be seen when we look at the wide range of outcomes for adults with ASD. Some individuals on the spectrum will be quite challenged throughout their lives and require supportive settings and many services, whereas others on the spectrum will require moderate supports during their lifetime. © 2025 National Art Education Association. All rights reserved.
Keywords: dept.sed

Art education and special education-Our journey together - Gerber, B.L.; Dorff, J.B.; Horoschak, L.J. (Reaching and Teaching Students with Special Needs Through Art, 2024)
This chapter brings the perspectives of three of SNAE's founding members who are also past presidents of both SNAE and DARTS. Beverly Levett Gerber, who combines the fields of special education and art education, begins our journey and describes our need to bridge professional differences in training and languages. She closes the chapter with a story of art educators and special educators learning together. Juliann B. Dorff describes our travels-the efforts, barriers, accomplishments, and the persistence needed to overcome roadblocks. Lynne J. Horoschak takes our journey in a new direction and describes a Saturday morning program that grew into a master's program focused on students with disabilities. © 2025 National Art Education Association. All rights reserved.
Keywords: dept.sed

Reaching and teaching students with special needs through art - Gerber, B.L.; Guay, D.M.; Burnette, J. (2024)
This second edition of Reaching and Teaching Students with Special Needs Through Art is written for art educators, special educators, and those who value the arts for students with special needs. It builds on teachers' positive responses to the first edition, and now combines over 700 years of the educational experience of arts and special educators who share their art lessons, behavior management strategies, and classroom stories. The revised second edition provides updated chapters addressing students with emotional/behavioral disabilities, learning disabilities, intellectual disabilities, physical disabilities, and visual and hearing impairments. The newly revised second edition includes chapters on students with autism spectrum disorder, preschool students, and students experiencing trauma. All chapters have been updated to include current definitions and language, recommended teaching strategies, art lesson adaptations, behavior management strategies, and references to related chapters. Follow-up activities are provided for further insights into each group of students. A new summary chapter connects how the authors' collaborations resulted in changes to two professional organizations. Since the first edition, many of the featured authors established the new Division of Visual and Performing Arts Education (DARTS) at the Council for Exceptional Children (CEC) and earlier, formed a new National Art Education Association (NAEA) Interest Group-Special Needs in Art Education (SNAE), now Arts in Special Education (ASE). This edition is ideal for preservice arts methods courses and education courses on accessibility and inclusion at the undergraduate and graduate levels. It continues to offer current yet proven best practices for reaching and teaching this ever-important population of students through the arts. © 2025 National Art Education Association. All rights reserved.
Pages: 319
Keywords: dept.sed

Curtains Up - Utilizing Assistive Technology for Inclusive Theater Experiences - Tucker, Lauren; Burnell, Nikki; Dalton, Morgan; Donenfeld, Marisa; Vadala, Catherine (Journal of the Arts and Special Education, 2024)
Keywords: dept.sed

Perspectives from an in-service teacher UDL action research project - Tucker, L. (Cases on Effective Universal Design for Learning Implementation Across Schools, 2024)
Including universal design for learning in graduate programs for in-service teachers is crucial to increasing the application of the framework in practice. This chapter will introduce an action research assignment within an American UDL graduate course and its impact on teacher practice and student learning. Eight case studies across disciplines and levels will be shared. During this process, teachers identified a classroom challenge, developed a UDL intervention, analyzed student data, and shared implications. In-service teacher reflections will be shared on the continued use of a UDL approach beyond their course work and its impact on their teaching practice. The chapter will begin with an introduction to the context of the implementation, investigation questions, methodology, case study presentation, discussion, and conclusion. © 2024, IGI Global.
Keywords: dept.sed

Foreword - Volkmar, F.R. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
Keywords: dept.sed

Definition of Autism and Autism Spectrum Disorder - Eren, R.B.; Gleeson, M.B. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
This chapter addresses the definition of autism spectrum disorder (ASD). A distinction is made between a clinical (medical) definition of ASD as defined in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and an educational eligibility classification of autism found in the Individuals with Disabilities Education Improvement Act (IDEA). The increase of prevalence of ASD is discussed with an opportunity to ponder the reason for this phenomenon. Several theories of causation of ASD are presented, offering an opportunity for thoughtful consideration of these theories found in current literature. General characteristics of ASD are described in the three domains of social interaction, communication, and behavior and are further illustrated by specific behaviors commonly seen in today’s classrooms. Characteristics focus not only on the variety of challenges individuals on the spectrum face but also the strengths many individuals with ASD bring to the classroom and community at large. Finally, a discussion of the future for individuals on the spectrum is emphasized through the wide range of possible outcomes for these individuals. Future opportunities seem to be improving for this population, although there remains a dearth of research on outcomes for adults with ASD. © 2024 Taylor & Francis Group. All rights reserved.
Keywords: dept.sed

Diagnosis and classification of autism spectrum disorder - Gleeson, M.B. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
This chapter introduces the evolution of the autism spectrum disorder (ASD) diagnosis. Beginning with the first Diagnostic and Statistical Manual of Mental Disorders (DSM) diagnostic criteria and ending with the current fifth edition (DSM-5) diagnostic criteria, readers will gain an in-depth perspective on changes in ASD diagnostic criteria over time and changes in classification of the disorder. Readers will be provided with an in-depth understanding of the current DSM-5 diagnostic criteria, as well as clinical specifiers and identification of level of support. Discussion is presented on some of the concerns and controversy surrounding the latest diagnostic changes and how those may impact school or support services. © 2024 Taylor & Francis Group. All rights reserved.
Keywords: dept.sed

Understanding behavior - Gleeson, M.B. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
Understanding behavior is paramount to educating and supporting individuals on the autism spectrum. This chapter provides an overview of applied behavior analysis including dispelling common misconceptions of the science, the ethics of behavior change, the process of completing a functional behavior assessment, including discussion on positive and negative reinforcement and the four functions of behavior, and using information gathered in a functional behavior assessment to plan supports for students. The chapter ends with an introduction to the evidence-based practice of antecedent-based interventions. © 2024 Taylor & Francis Group. All rights reserved.
Keywords: dept.sed

Facilitating interaction with police during routine traffic stops for persons with ASD - Grindle, H.; Sassu, K.A.; Dooley, J.M.; Farmer, E.B.; Volkmar, F.R. (Journal of Autism and Developmental Disorders, 2024)
A product of ASD socio-communicative-deficits and insufficient police training related to autism, ASD-police interactions have the potential to become problematic, with negative outcomes for ASD individuals and police alike. Thus, the combination of police acclimation, simulatory experience for drivers with ASD and the introduction of Connecticut’s recent Blue Envelope could improve overall experiences for drivers. A simulated routine traffic stop practice event, utilising pre- and post- measures was conducted in an effort to quantify drivers’ feelings about current and future interactions with police. Our prediction that participants would experience a statistically significant improvement in anxiety, comfort and self-perceived knowledge levels about future ASD-police interactions immediately following the intervention was confirmed. Our prediction that initially significant disparities between participants with and without police experience – those with previous police encounters versus those that don’t - would become not significant immediately following the intervention was disconfirmed. While the longitudinal data suggested that improved post-intervention ASD psychological measures remained statistically significant in the long-term, the sample responses to our long-term questionnaire were too few in number to make any definitive conclusions. It is suggested that practice traffic stops such as these could benefit both drivers with ASD and law enforcement nationwide. It is further suggested that police officer curriculums should include additional training regarding special populations. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.
Keywords: ASD; ASD-police Interaction; Blue Envelope Program; Driving; Pullover; Simulation; dept.edu; dept.sed; peer-reviewed

Impacts of an assistive technology graduate program: a case study - Tucker, Lauren (Assistive Technology Outcomes and Benefits (ATOB), 2024)
Alumni from an Assistive Technology (AT) graduate program were invited to complete a survey and participate in focus groups to share how they are using the knowledge gained from their graduate degree and its impact on their professional careers. The sample of 27 alumni spanned seven years and a variety of professional backgrounds. This qualitative single-case study revealed impacts on careers, professional skill development, and technology skills after graduation. Participants also connected this later skill development to their concrete learning experiences within the graduate program.
Keywords: assistive technology; dept.sed; graduate program; peer-reviewed; perspectives; special education

Letter to the editor: Supporting drivers with autism and police officer interactions-Connecticut’s blue envelope program - Gleeson, M.B.; Grindle, H.; Gleeson, M.M. (Journal of Autism and Developmental Disorders, 2024)
The rising prevalence of autism spectrum disorder (ASD) has led to increased efforts to support individuals with ASD across numerous aspects of life, including driving. While obtaining a driver’s license substantially impacts quality of life and independence, it also creates distinct challenges for those with ASD. Challenges surrounding social communication, executive functioning, and sensory sensitivities are particularly evident when considering interactions between drivers with ASD and law enforcement personnel. Connecticut’s Blue Envelope Program aims to improve interactions between drivers with and ASD law enforcement by providing instructions for officers and drivers to follow during routine traffic stops on a physical, blue colored, envelope. The instructional guidelines aim to assist officers in understanding and appropriately responding to common ASD-related behaviors which may be otherwise misinterpreted and includes accommodations officers could consider during a stop. Additionally, the envelope outlines clear steps for drivers with ASD to follow through the stop as to support predictability and expectations. The widespread acceptance, efficacy and popularity of the Blue Envelope program underscores the importance of increasing awareness and understanding of ASD among law enforcement and the need for more supports to aid in these increasing interactions. Discussion is offered on a broader implementation of this program to support individuals with ASD and officers, while improving the outcomes of interactions. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.
Keywords: Autism; Blue envelope; Driving; Law enforcement; Police officers; dept.sed

Whither Asperger’s post DSM-5? An opinion piece - Volkmar, F.R.; Woodbury-Smith, M. (Review Journal of Autism and Developmental Disorders, 2024)
Although first described in 1944 (the year the description of infantile autism), Asperger’s syndrome attracted little attention until the publication by Lorna Wing in early 1980. Over time, different views of the definition of Asperger’s syndrome developed. By the time of the Third Edition of the American Psychiatric Association’s Diagnostic and Statistical Manual and the Tenth Edition of the World Health Organization’s International Classification of Disease, enough information had accumulated to include the condition within the broader autism category. Asperger’s syndrome remained a focus of research interest and debate until its exclusion in the DSM-5 in 2013. We argue that the decision to remove Asperger’s syndrome 10 years ago as a distinct condition was premature. A discussion of the tensions around defining Asperger’s and concerns now arising due to the lack of this diagnostic category for new cases is provided. © 2024, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Asperger’s disorder; Autism spectrum disorder; Autistic disorder; Classification; DSM-5; dept.sed; peer-reviewed